Environmental chemistry microscale laboratory experiments - Ibanez, Jorge G.; Hernandez-Esparza, Margarita; Doria-Serrano, Carmen; Fregoso, Infante, Arturo; Singh, Mono Mohan (New York, NY, USA Springer Science+Business Media, LLC, 2008)
Environmental issues are growing in importance to the most important political, social, legal, and economic decisions. The book presents chemical analyses of our most pressing waste, pollution, and resource problems for the undergraduate or graduate student. The distinctive holistic approach provides both a solid ground in theory, as well as a laboratory manual detailing introductory and advanced experimental applications. The laboratory procedures are presented at microscale conditions, for minimum waste and maximum economy.This work fulfills an urgent need for an introductory text in environmental chemistry combining theory and practice, and is a valuable tool for preparing the next generation of environmental scientists.
Experiments -- Water Characterization -- Dissolved Oxygen in Water -- Alkalinity and Buffering Capacity of Water -- Aqueous Carbonate Equilibria and Water Corrosiveness -- The Point of Zero Charge of Oxides -- Experimental Transitions in E vs pH (or Pourbaix) Diagrams -- Air Oxidation of Metal Ions -- Photoassisted Reduction of Metal Complexes -- Anionic Detergents and o-Phosphates in Water -- Halogenated Hydrocarbons and the Ozone Layer Depletion -- Acid Mine (or Acid Rock) Drainage -- Electrochemical Treatment of Gas Pollutants -- Electrochemical Treatment of Liquid Wastes -- Electrochemical Treatment of Polluted Soils -- Removal of Nitric Oxide by Complex Formation -- Photocatalytic Remediation of Pollutants -- Chemical Mineralization of Pollutants Through the Fenton Reaction -- Production and Analysis of Chloramines -- Production and Analysis of Chlorine Dioxide -- Metal Ion Recovery By Cementation -- Green Chemistry: The Recovery and Reuse of Sulfur Dioxide (Obendrauf's Method) -- Microorganisms in Soil, Water, and Air -- Toxicity Assay Using Bacterial Growth -- Wastewater Disinfection.
Includes bibliographical references.
Keywords: Environmental chemistry; Environmental chemistry -- Experiments; Chemical microscopy